Optimization of a microreactor core's dimensions using metaheuristic methods - Nicolas Santana; Alexandre Caldeira; Angelo Passaro; Lamartine Guimaraes (Brazilian Journal of Radiation Sciences)
This article proposes the use of the multi-group diffusion equations with four groups to determine the dimensions of the microreactor of the TERRA project. With this intent, the values of the radius and height of the cylinder that represents the core, as well as its enrichment were optimized through a framework called LOF. This tool has several metaheuristics methods already implemented, which provides a considerable time gain. So any particular method implemented, or a combination of some of them, could be utilized without any concerns regarding implementation time. In addition to the application of the metaheuristic methods for the proposed optimization, there was also a concern about altering the search parameters used in each of the metaheuristics, which eventually caused an improvement in the results. With this method, the radius and height dimensions achieved were quite reasonable for a microreactor. As for the enrichment, the value of 19.75% was achieved, limited by the Non-Proliferation Treaty.